Buccal bone deficiency in fresh extraction sockets: a prospective single cohort study. Issue 7 (31st March 2014) - Barone, Antonio; Ricci, Massimiliano; Romanos, Georgios E.; Tonelli, Paolo; Alfonsi, Fortunato; Covani, Ugo
Abstract Objective The purpose of this prospective single cohort study was to evaluate the use of xenograft and collagen membranes in treating full or partial buccal bone defects of fresh extraction sockets in the esthetic zone. Materials and methods Thirty‐three patients requiring tooth extraction in the anterior maxillary area and showing a complete or partial buccal bone plate deficiency (more than 2 mm) were consecutively enrolled and treated. Corticocancellous porcine bone and platelet‐rich fibrin (PRF) with a collagen membrane were used to graft the extraction sockets, and the membranes were left exposed to the oral cavity with a secondary soft tissue healing. The outcome variables were as follows: width of keratinized mucosa, facial soft tissue levels, clinical bone changes (measured with a clinical splint), implant and prosthesis failures, and peri‐implant marginal bone changes. Results All treated sites allowed the placement of implants; the width of keratinized mucosa at the mid‐facial aspect showed an increase of 2.3 mm 5 months after the grafting procedure, and its value was 3.2 ± 0.6 mm at 1‐year follow‐up. The mean values of the facial soft tissue level indicated an increase over time. The bone level showed an improvement of 0.8 ± 0.1 mm and 0.7 ± 0.1 mm at mesial and distal sites, respectively, when compared to the baseline measurements. Finally, in the palatal area, no bone changes were observed. No implant failed during the entire observation period. Conclusions Findings from this study showed that xenograft and PRF, used for ridge preservation of the extraction sockets with buccal bone plate dehiscence in the esthetic zone, can be considered effective in repairing bone defects before implant placement. The secondary soft tissue healing over the grafted sockets did not compromise bone formation; moreover, the soft tissue level and the width of keratinized gingiva showed a significant improvement over time.